1999
DOI: 10.1007/s001250051163
|View full text |Cite
|
Sign up to set email alerts
|

Defective regulation of phosphatidylinositol-3-kinase gene expression in skeletal muscle and adipose tissue of non-insulin-dependent diabetes mellitus patients

Abstract: Despite intensive efforts, the nature of the molecular defects leading to the development of Type II (noninsulin-dependent) diabetes mellitus is poorly understood. Whereas both alterations in insulin secretion and action are involved in established diabetes [1,2], it has been suggested that defects in insulin action precede the onset of the disease [3]. There is good evidence that insulin resistance in Type II diabetes is dependent, at least in part, on genetic factors [4,5]. The mutations identified so far in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
53
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 40 publications
10
53
1
2
Order By: Relevance
“…Moreover, it has been reported that the induction of GLUT4 (20,21) and hexokinase II (22) expression in response to hyperinsulinemia is impaired in skeletal muscle of type 2 diabetic patients. Recently, we have demonstrated that the regulation by insulin of the p85␣ regulatory subunit of PI3K (p85␣PI3K) is also altered in muscle and adipose tissue of patients with type 2 diabetes (23). Taken together, these data suggest that the regulation of a cluster of genes involved in insulin action and glucose metabolism may be affected in type 2 diabetes.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, it has been reported that the induction of GLUT4 (20,21) and hexokinase II (22) expression in response to hyperinsulinemia is impaired in skeletal muscle of type 2 diabetic patients. Recently, we have demonstrated that the regulation by insulin of the p85␣ regulatory subunit of PI3K (p85␣PI3K) is also altered in muscle and adipose tissue of patients with type 2 diabetes (23). Taken together, these data suggest that the regulation of a cluster of genes involved in insulin action and glucose metabolism may be affected in type 2 diabetes.…”
mentioning
confidence: 81%
“…None of the obese subjects had impaired glucose tolerance as assessed by classic oral glucose tolerance test. The metabolic data of some of these subjects (all of the control and type 2 diabetic subjects and six of the nine obese patients) have been presented in a previous study (23). An unrelated group of healthy subjects (seven women and one man, age 25 Ϯ 1 years, BMI 22 Ϯ 1 kg/m 2 ) served as control subjects for a group of type 1 diabetic patients (five women and four men, age 33 Ϯ 3 years, BMI 23 Ϯ 1 kg/m 2 , duration of diabetes 16 Ϯ 3 years, C-peptide Ͻ0.05 ng/ml) with HbA 1c (9.2 Ϯ 0.3%) similar to that in the type 2 diabetic subjects (10.9 Ϯ 0.3%, P ϭ 0.252).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, altered insulin action, often characterized by a deregulation of the PI3K cascade, is found in both diabetic and obese subjects (17)(18)(19). This pathway mediates also the effects of insulin on glucose and lipid homeostasis by controlling the expression of a series of genes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a targeted disruption of the gene encoding the p85α regulatory subunit of PI 3-kinase show increased insulin sensitivity and hypoglycaemia, due to increased glucose uptake in skeletal muscle and adipocytes via signalling through the p50α alternative splice variant of the p85α gene [26]. The mRNA expression of p85α has been reported to be similar in adipose tissue from lean versus obese humans [27]. However in our study, protein expression of the p85α regulatory subunit of PI 3-kinase was reduced by 55% in adipocytes from obese women.…”
Section: Discussionmentioning
confidence: 99%